1990
DOI: 10.1088/0953-8984/2/1/002
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structural determination of the quasi-commensurate phase of barium sodium niobate

Abstract: Inorder to provide anaccurate basis forthe interpretationofthe physical properties of this complex incommensurate system, the structure of the room temperature quasicommensurate phase of barium sodium niobate is determined by taking into account. for the first time, the satellite reflections present in the diffraction spectrum of this material. The quasi-commensurate phase considered is assimilated to a strictly commensurate phase, the satellite reflections being considered as superlattice reflections and refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
44
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 15 publications
13
44
0
1
Order By: Relevance
“…Initial inspection of both data sets revealed the deficiency of the previous assignment of tetragonal symmetry based on (lower resolution) ambient temperature laboratory PXRD data; 40 the structure is orthorhombic over the entire measured temperature range between 20 -600 K. Closer inspection of the PND data revealed additional peaks of low intensity at longer d-spacing which do not correspond to likely impurity phases but which indicate the presence of a large orthorhombic superstructure. This superstructure is consistent with the Bbm2 model of Labbé and co-workers 38 which has a ≈ 2√2 a TTB , b ≈ √2 a TTB and c ≈ 2 c TTB expansions, Figure 3(a), and is the same structure reported for Ba 4 La 2 Ti 4 Nb 6 O 30 . 21 Rietveld refinement of the low temperature data PND data indicates that the atom positions in this compound are close to those determined for BNN, see electronic supporting information (ESI) Figures S1-2 and Tables S1-3.…”
Section: Methodssupporting
confidence: 89%
“…Initial inspection of both data sets revealed the deficiency of the previous assignment of tetragonal symmetry based on (lower resolution) ambient temperature laboratory PXRD data; 40 the structure is orthorhombic over the entire measured temperature range between 20 -600 K. Closer inspection of the PND data revealed additional peaks of low intensity at longer d-spacing which do not correspond to likely impurity phases but which indicate the presence of a large orthorhombic superstructure. This superstructure is consistent with the Bbm2 model of Labbé and co-workers 38 which has a ≈ 2√2 a TTB , b ≈ √2 a TTB and c ≈ 2 c TTB expansions, Figure 3(a), and is the same structure reported for Ba 4 La 2 Ti 4 Nb 6 O 30 . 21 Rietveld refinement of the low temperature data PND data indicates that the atom positions in this compound are close to those determined for BNN, see electronic supporting information (ESI) Figures S1-2 and Tables S1-3.…”
Section: Methodssupporting
confidence: 89%
“…The same sequences of transitions were reported for the well known ferroelectric Ba 2 NaNb 5 O 15 TTB-type material [25]. The crystal structure of Ba 2 NaNb 5 O 15 [26] showed the existence of quasi-commensurability at room temperature. In fact, there are several distinct incommensurate phases differing in the number of wave directions of the modulations [25,26].…”
Section: Introductionsupporting
confidence: 74%
“…Schneck et al [44] and Labbe et al [45] revealed the incommensurate character of the crystal structure of SBN, which is similar to the previously discovered incommensurability in BNN [46] and appears in combination with ferroelastic properties. [47] Simon et al [48] showed that SBN crystals exhibit anisotropic dielectric behavior.…”
Section: Wwweurjicorg Full Papersupporting
confidence: 67%